Serum Matrix Metalloproteinase-9 Level and Previous Disease Activity in Relapsing-Remitting Multiple Sclerosis - Eman Hamdy; Ismail Ramdan; Jaidaa Mekky; Aya Abdel Gleel; Dina Gaber (International Clinical Neuroscience Journal, 2023)
Background: Matrix metalloproteinase-9 (MMP-9) is a marker of blood-brain barrier destruction, that is elevated during clinical relapses in multiple sclerosis (MS). In between relapses, MMP-9 levels decline but remain higher than the normal population. This study aimed to investigate the relation between serum MMP-9 level and disease activity in MS during relapse-free periods. Methods: This was a retrospective study conducted on adult patients with relapsing-remitting MS (RRMS) whose last relapse was≥1 month ago. Serum MMP-9 was withdrawn at the time of recruitment and correlated with parameters of disease activity. Results: Of the 40 patients recruited, 75% were women. The mean age was 36.2±8.4 years, and the mean disease duration was 7 years. Patients’ median Expanded Disability Status Scale (EDSS) was 3.5 (IQR: 2.5-5.25), the median duration since the last relapse was 3 months, and the median duration since last corticosteroid administration was 6 months. On multivariate regression analysis, there was a significant association between serum MMP-9 levels and duration since the last relapse (B: -0.004, 95% CI: -0.007- -0.002, P=0.001) as well as duration since the last corticosteroid intake (B: -0.003, 95% CI: -0.006- -0.001, P=0.005). Conclusion: Serum MMP-9 levels correlated with the duration since last relapse and duration since last corticosteroids administration during relapse-free periods.